The Prevention of Landslides Using the Analytic Hierarchy Process (AHP) in a Geographic Information System (GIS) Environment in the Province of Larache, Morocco - El Hamdouni, Ikram; Ait Brahim, Lahsen; El Mahsani, Abderahman; Abdelouafi, Abdellah (Geomatics and Environmental Engineering, 2022)
Landslides are one of the natural hazards that many countries around the world are facing. In Morocco, the Rif regions are the most affected by these phenomena. Each year they cause enormous damage to the road network and infrastructure, especially in our study region, the province of Larache. The study region is subject to several opening up and road construction projects, which is why it is necessary to predict and identify the most vulnerable areas beforehand, in order to propose measures and techniques which are adequate for protection and reinforcement. The main goal of this study is to develop a susceptibility map to ground movements using a multi-criteria spatial assessment approach, and in order to reduce subjectivity, we have used a method for analyzing such complex decisions, which is the analytic hierarchy process (AHP) implemented in the geographic information system (GIS). Seven factors have been considered as conditioning factors in the occurrence of landslides, which are: lithology, fracturing density, slope, aspect, land use, density of the hydrographic network, and altitude. To verify the results obtained, we performed a correlation analysis of ground movements, already inventoried and verified in the field, with the susceptibility classes that were calculated. This analysis is accompanied by a statistical study.